Alkali metal loaded cobalt-based catalyst and preparation method and application thereof

By using alkali metal-supported cobalt-based catalysts, the problem of excessive catalytic hydrogenation of Co-based catalysts was solved, which significantly improved the selectivity of ethanol and the conversion of carbon dioxide, and achieved a more efficient carbon dioxide hydrogenation and ethanol production reaction.

CN119909685AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411979951.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing Co-based catalysts are too strong in the hydrogenation of carbon dioxide, resulting in the main products being CH4 and CO, and the selectivity of ethanol is low.

Method used

An alkali metal-supported cobalt-based catalyst is used, which consists of cobalt aluminum spinel and alkali metals supported thereon, and contains Co0 and CoAl2O4 bicatalytic active sites. By regulating the proportion of cobalt aluminum and the hydrogen pre-reduction temperature, appropriate catalytic active sites are formed to improve the selectivity of ethanol.

Benefits of technology

It significantly improves the conversion rate of carbon dioxide and the selectivity of ethanol, inhibits excessive hydrogenation reaction, and promotes the coupling reaction of carbon-carbon bonds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119909685A_ABST
    Figure CN119909685A_ABST
Patent Text Reader

Abstract

The invention provides an alkali metal loaded cobalt-based catalyst as well as a preparation method and application thereof, and relates to the technical field of preparation of a catalyst for preparing ethanol through hydrogenation of carbon dioxide. The active center of the catalyst is cobalt metal in a cobalt aluminate spinel structure, the catalyst contains Co0 and CoAl2O4 double catalytic active sites, and alkali metal is further introduced, so that the conversion rate of carbon dioxide and the selectivity of ethanol can be remarkably improved. In the carbon dioxide hydrogenation reaction, the conversion rate of carbon dioxide is high, and the selectivity of ethanol is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon dioxide hydrogenation to ethanol catalyst preparation, and in particular to an alkali metal-loaded cobalt-based catalyst and a preparation method and application thereof. Background Art

[0002] As the current carbon dioxide (CO 2 ) has led to an intensified greenhouse effect and has had a huge impact on the global ecosystem. 2 The utilization of coupled “green hydrogen” can be converted into high value-added chemical products through catalytic hydrogenation, which is of great significance for reducing CO 2 Emissions and improving the ecosystem have important practical significance.

[0003] In recent years, there have been a lot of studies on CO 2 There have been many reports on the research of hydrogenation synthesis of methanol, and it has reached the initial industrial scale. 2 There are relatively few reports on the direct conversion of methanol into ethanol by hydrogenation. As one of the most basic chemical products, ethanol is widely used in various fields and can be used as a gasoline additive, a solvent for material synthesis, and an industrial intermediate. Compared with methanol, ethanol has a higher energy density and a higher calorific value of combustion. Therefore, CO 2 The hydrogenation reaction to synthesize ethanol is a process route with greater industrial value.

[0004] From CO 2 It can be seen from the reaction mechanism of hydrogenation synthesis of ethanol that the formyl (·CHO) intermediate produced in the reaction process is difficult to break the CO bond and couple the CC bond in time, so the methane (CH 4 ), carbon monoxide (CO), methanol and other products are inevitable. Based on this, in CO 2 In the hydrogenation reaction to ethanol, achieving high ethanol selectivity and yield requires coordinating the CO 2 At present, according to the classification of active components, CO 2 Catalysts for hydrogenation of ethanol mainly include precious metal-based catalysts, Co-based catalysts, Cu-based catalysts and Mo-based catalysts. Among them, Co-based catalysts have been widely studied due to their advantages such as strong hydrogenation ability, CC bond coupling ability and low price. Chinese patent CN106311281A uses basic nickel carbonate as a template, introduces transition metal molybdenum by ion exchange, then impregnates alkali metal potassium, and finally sulfides to obtain a ternary metal sulfide catalyst with a layered structure. The catalytic evaluation results of the catalyst show that the molar fraction of ethanol in the total alcohol is 43%, and there is still a lot of room for improvement. According to current research, Co-based catalysts catalyze CO2 The key to hydrogenation reaction to produce ethanol is to reduce the hydrogenation performance of metal Co, so that CO 2 It can be converted to form a CO intermediate, which can then be converted to ethanol via a CC coupling reaction.

[0005] In summary, in the current CO2 hydrogenation reaction, the Co-based catalyst still has the problem of Co catalytic hydrogenation being too strong, and the main product of the reaction is CH 4 And the disadvantages include low selectivity of CO and ethanol. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a catalyst for preparing ethanol by hydrogenating carbon dioxide and a preparation method thereof. The catalyst of the present invention has a high conversion rate of carbon dioxide and a high selectivity for ethanol in the carbon dioxide hydrogenation reaction.

[0007] One of the objects of the present invention is to provide an alkali metal-supported cobalt-based catalyst.

[0008] The second object of the present invention is to provide a method for preparing the alkali metal-supported cobalt-based catalyst.

[0009] The third object of the present invention is to provide an application of the alkali metal-supported cobalt-based catalyst.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] In a first aspect, the present invention provides an alkali metal-supported cobalt-based catalyst, comprising a cobalt aluminum spinel and an alkali metal supported on the cobalt aluminum spinel, wherein a portion of the active center cobalt of the cobalt aluminum spinel is CoAl 2 O 4 The spinel structure exists in the form of a spinel structure, and the other part is zero-valent Co 0 Form exists.

[0012] The active center of the catalyst of the present invention is the cobalt metal in the cobalt aluminum spinel structure, and it also contains Co 0 and CoAl 2 O 4 Dual catalytic active sites and the further introduction of alkali metals can significantly improve the conversion rate of carbon dioxide and the selectivity of ethanol.

[0013] In some embodiments, the loading amount of the alkali metal is 5 wt% to 15 wt% based on the mass of the cobalt aluminum spinel.

[0014] In some embodiments, the alkali metal includes one of lithium, sodium, and potassium.

[0015] In some embodiments, CoAl 2 O4 Cobalt in the form of spinel structure and zero-valent Co 0 The molar ratio of cobalt in the form of is 15:1 to 2:1.

[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned alkali metal-supported cobalt-based catalyst, comprising the following steps:

[0017] S1. Dissolve cobalt salt and aluminum isopropoxide in ethylene glycol, stir under heating conditions, wash with ethanol by centrifugation, and dry in a vacuum drying oven; calcine the dried powder in a muffle furnace at high temperature to obtain cobalt aluminum spinel;

[0018] S2. Dissolve cobalt aluminum spinel and alkali metal chloride in deionized water, stir evenly, stir under heating conditions to completely evaporate the deionized water, and then place in a vacuum drying oven for drying; place the dried powder in a muffle furnace for high-temperature calcination, and then perform hydrogen reduction treatment to obtain an alkali metal-loaded cobalt-based catalyst.

[0019] Step S1:

[0020] In some embodiments, in step S1, the cobalt salt includes one or more of cobalt nitrate or its hydrate, cobalt carbonate or its hydrate, and cobalt sulfate or its hydrate;

[0021] In some embodiments, in step S1, the molar ratio of cobalt in the cobalt salt to aluminum in aluminum isopropoxide is 1:2 to 1:8;

[0022] In some embodiments, in step S1, the stirring heating temperature is 30°C to 90°C, the stirring speed is 200rpm to 600rpm, and the stirring time is 2 to 6h;

[0023] In some embodiments, in step S1, the centrifugal speed is 2000 rpm to 6000 rpm, and the number of centrifugal washings is 2 to 5 times;

[0024] In some embodiments, in step S1, the drying temperature is 30°C to 100°C, and the drying time is 3h to 15h.

[0025] In some embodiments, in step S1, the high temperature calcination temperature is 400°C to 800°C, the calcination time is 1h to 8h, and the heating rate is 1°C / min to 10°C / min.

[0026] Step S2:

[0027] In some embodiments, in step S2, the alkali metal chloride includes one or more of lithium chloride, sodium chloride, and potassium chloride;

[0028] In some embodiments, in step S2, the amount of alkali metal added is 5 wt%-15 wt% based on the mass of cobalt aluminum spinel.

[0029] In some embodiments, in step S2, the heating and stirring temperature is 50°C to 100°C, and the stirring rate is 200rpm to 600rpm;

[0030] In some embodiments, in step S2, the drying temperature is 30°C to 100°C, and the drying time is 3h to 15h.

[0031] In some embodiments, in step S2, the high temperature calcination temperature is 200°C to 800°C, the calcination time is 1h to 8h, and the heating rate is 1°C / min to 10°C / min.

[0032] In some embodiments, in step S2, the conditions for hydrogen reduction treatment are: space velocity of 3000 mL / g / h to 10000 mL / g / h, reduction temperature of 250° C. to 800° C., and reduction time of 1 h to 6 h.

[0033] In a third aspect, the present invention provides an application of the above-mentioned alkali metal-supported cobalt-based catalyst in the preparation of ethanol by catalytic reaction of carbon dioxide hydrogenation.

[0034] The catalyst is tableted, crushed and sieved before being loaded into a fixed bed reactor for carbon dioxide hydrogenation reaction, wherein the sieved particle size is 10-60 meshes.

[0035] Preferably, the conditions of the catalytic reaction are: reaction temperature of 200-400°C, reaction pressure of 2-4 MPa, total space velocity of raw gas of 3000-8000 mL / g / h, and the gas used is CO 2 and H 2 A mixture of CO 2 and H 2 The volume ratio is 1:1~4.

[0036] The catalyst is subjected to hydrogen pre-reduction treatment before the reaction test, and the reduction conditions are: hydrogen space velocity of 3000mL / g / h to 10000mL / g / h, reduction temperature of 250°C to 400°C, and reduction time of 1h to 6h.

[0037] Technical effect:

[0038] (1) The preparation method provided by the present invention is simple, the operation process is convenient, and the price and cost are low. The prepared catalyst has a high conversion rate of carbon dioxide and a high selectivity for ethanol in the carbon dioxide hydrogenation reaction.

[0039] (2) The alkali metal-modified cobalt-based catalyst prepared by the present invention increases the reduction temperature of cobalt by preforming a cobalt-aluminum spinel structure, so that the formation of Co in a reducing atmosphere is avoided. 0 At the same time, by adjusting the reduction temperature, the CoAl that is not completely reduced exists during the reaction. 2 O 4 and cobalt, i.e., Co 0 -CoAl 2 O 4 Dual catalytic sites.

[0040] (3) The alkali metal-modified cobalt-based catalyst prepared by the present invention can flexibly adjust the Co by adjusting the pre-reduction temperature and the ratio of cobalt to aluminum. 0 -CoAl 2 O 4 The number of dual catalytic sites can effectively inhibit over-hydrogenation reactions while promoting carbon-carbon bond coupling reactions, thereby significantly improving ethanol selectivity;

[0041] (4) The alkali metal-modified cobalt-based catalyst prepared by the present invention improves the selectivity of ethanol and further improves the adsorption capacity of the catalyst for carbon dioxide by introducing alkali metal elements, thereby improving the conversion rate of carbon dioxide.

[0042] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is the X-ray diffraction (XRD) spectrum of the catalyst prepared in Example 1. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0045] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0046] Example 1

[0047] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 3.5 g of aluminum isopropoxide (0.017 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0048] (2) calcining the powder at 700° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min to obtain cobalt aluminum spinel;

[0049] (3) 500 mg of cobalt aluminum spinel and the calculated mass fraction of lithium chloride were dissolved in deionized water, stirred evenly, stirred at 80° C. and 500 rpm to completely evaporate the deionized water, and then placed in a vacuum drying oven at 80° C. for 12 h; the lithium loading was 5%;

[0050] (4) calcining the powder in a muffle furnace at 400° C. for 4 h at a heating rate of 2° C. / min to prepare a catalyst;

[0051] The X-ray diffraction (XRD) spectrum of the catalyst is as follows: Figure 1 As shown in the figure, it can be seen that there is a spinel structure in the catalyst, and after proper reduction, CoAl 2 O 4 It coexists with Co species to construct dual catalytic active sites, and the molar ratio of the two is 10:1.

[0052] The catalyst was pre-reduced with hydrogen before the reaction test, with a space velocity of 8000 mL / g / h, a pretreatment condition of 400°C, and a reduction time of 4 h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, with a reaction temperature of 260°C, a reaction pressure of 3 MPa, a total space velocity of 6000 mL / g / h, and a gas of CO. 2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0053] Example 2: Change H 2 Pre-reduction temperature is 600℃

[0054] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 3.5 g of aluminum isopropoxide (0.017 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0055] (2) calcining the powder at 700° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min to obtain cobalt aluminum spinel;

[0056] (3) 500 mg of cobalt aluminum spinel and the calculated mass fraction of lithium chloride were dissolved in deionized water, stirred evenly, stirred at 80° C. and 500 rpm to completely evaporate the deionized water, and then placed in a vacuum drying oven at 80° C. for 12 h; the lithium loading was 5%;

[0057] (4) calcining the powder in a muffle furnace at 400° C. for 4 h at a heating rate of 2° C. / min to prepare a catalyst;

[0058] The catalyst was pre-reduced with hydrogen before the reaction test, with a space velocity of 8000 mL / g / h, a pretreatment condition of 600°C, and a reduction time of 4 h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, with a reaction temperature of 260°C, a reaction pressure of 3 MPa, a total space velocity of 6000 mL / g / h, and a gas of CO. 2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0059] Example 3 Changing the type of alkali metal to sodium

[0060] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 3.5 g of aluminum isopropoxide (0.017 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0061] (2) calcining the powder at 700° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min to obtain cobalt aluminum spinel;

[0062] (3) 500 mg of cobalt aluminum spinel and sodium chloride (calculated by mass fraction) were dissolved in deionized water, stirred evenly, stirred at 80° C. and 500 rpm to completely evaporate the deionized water, and then placed in a vacuum drying oven at 80° C. for 12 h; the sodium loading was 5%;

[0063] (4) calcining the powder in a muffle furnace at 400° C. for 4 h at a heating rate of 2° C. / min to prepare a catalyst;

[0064] The catalyst was pre-reduced with hydrogen before the reaction test, with a space velocity of 8000 mL / g / h, a pretreatment condition of 600°C, and a reduction time of 4 h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, with a reaction temperature of 260°C, a reaction pressure of 3 MPa, a total space velocity of 6000 mL / g / h, and a gas of CO. 2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0065] Example 4: Changing the type of alkali metal to potassium

[0066] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 3.5 g of aluminum isopropoxide (0.017 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0067] (2) calcining the powder at 700° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min to obtain cobalt aluminum spinel;

[0068] (3) 500 mg of cobalt aluminum spinel and calculated mass fraction of potassium chloride were dissolved in deionized water, stirred evenly, stirred at 80° C. and 500 rpm to completely evaporate the deionized water, and then placed in a vacuum drying oven at 80° C. for 12 h; the potassium loading was 5%;

[0069] (4) calcining the powder in a muffle furnace at 400° C. for 4 h at a heating rate of 2° C. / min to prepare a catalyst;

[0070] The catalyst was pre-reduced with hydrogen before the reaction test, with a space velocity of 8000 mL / g / h, a pretreatment condition of 600°C, and a reduction time of 4 h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, with a reaction temperature of 260°C, a reaction pressure of 3 MPa, a total space velocity of 6000 mL / g / h, and a gas of CO. 2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0071] Example 5 Changing the molar ratio of cobalt to aluminum to 1:2

[0072] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 1.4 g of aluminum isopropoxide (0.0068 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0073] (2) calcining the powder at 700° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min to obtain cobalt aluminum spinel;

[0074] (3) 500 mg of cobalt aluminum spinel and calculated mass fraction of potassium chloride were dissolved in deionized water, stirred evenly, stirred at 80° C. and 500 rpm to completely evaporate the deionized water, and then placed in a vacuum drying oven at 80° C. for 12 h; the potassium loading was 5%;

[0075] (4) calcining the powder in a muffle furnace at 400° C. for 4 h at a heating rate of 2° C. / min to prepare a catalyst;

[0076] The catalyst was pre-reduced with hydrogen before the reaction test, with a space velocity of 8000 mL / g / h, a pretreatment condition of 600°C, and a reduction time of 4 h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, with a reaction temperature of 260°C, a reaction pressure of 3 MPa, a total space velocity of 6000 mL / g / h, and a gas of CO. 2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0077] Comparative Example 1: Changing the molar ratio of cobalt to aluminum to 1:1

[0078] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 0.7 g of aluminum isopropoxide (0.0034 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0079] (2) calcining the powder at 700° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min to obtain cobalt aluminum spinel;

[0080] (3) 500 mg of the carrier and the calculated mass fraction of potassium chloride were dissolved in deionized water, stirred evenly, stirred at 80° C. and 500 rpm to completely evaporate the deionized water, and then placed in a vacuum drying oven at 80° C. for 12 h; the potassium loading was 5%;

[0081] (4) calcining the powder in a muffle furnace at 400° C. for 4 h at a heating rate of 2° C. / min to prepare a catalyst;

[0082] The catalyst was pre-reduced with hydrogen before the reaction test, with a space velocity of 8000 mL / g / h, a pretreatment condition of 600°C, and a reduction time of 4 h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, with a reaction temperature of 260°C, a reaction pressure of 3 MPa, a total space velocity of 6000 mL / g / h, and a gas of CO. 2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0083] Comparative Example 2: Changing the pre-reduction temperature of hydrogen

[0084] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 3.5 g of aluminum isopropoxide (0.017 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0085] (2) calcining the powder at 700° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min to obtain cobalt aluminum spinel;

[0086] (3) 500 mg of the carrier and the calculated mass fraction of potassium chloride were dissolved in deionized water, stirred evenly, stirred at 80° C. and 500 rpm to completely evaporate the deionized water, and then placed in a vacuum drying oven at 80° C. for 12 h; the potassium loading was 5%;

[0087] (4) calcining the powder in a muffle furnace at 400° C. for 4 h at a heating rate of 2° C. / min to prepare a catalyst;

[0088] The catalyst was pre-reduced with hydrogen before the reaction test, with a space velocity of 8000 mL / g / h, a pretreatment condition of 200°C, and a reduction time of 4 h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, with a reaction temperature of 260°C, a reaction pressure of 3 MPa, a total space velocity of 6000 mL / g / h, and a gas of CO. 2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0089] Comparative Example 3: Changing aluminum isopropoxide to aluminum oxide

[0090] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 1.73 g of aluminum oxide (0.017 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0091] (2) calcining the powder in a muffle furnace at 700° C. for 4 h at a heating rate of 2° C. / min to prepare an alumina-supported cobalt catalyst;

[0092] (3) 500 mg of the carrier and the calculated mass fraction of potassium chloride were dissolved in deionized water, stirred evenly, stirred at 80° C. and 500 rpm to completely evaporate the deionized water, and then placed in a vacuum drying oven at 80° C. for 12 h; the potassium loading was 5%;

[0093] (4) calcining the powder in a muffle furnace at 400° C. for 4 h at a heating rate of 2° C. / min to prepare a catalyst;

[0094] The catalyst was pre-reduced with hydrogen before the reaction test, with a space velocity of 8000 mL / g / h, a pretreatment condition of 600°C, and a reduction time of 4 h. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor for reaction performance evaluation, with a reaction temperature of 260°C, a reaction pressure of 3 MPa, a total space velocity of 6000 mL / g / h, and a gas of CO.2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0095] Comparative Example 4: No Alkali Metal Modification

[0096] (1) 1 g of cobalt nitrate hexahydrate (0.0034 mol) and 3.5 g of aluminum isopropoxide (0.017 mol) were dissolved in 50 mL of ethylene glycol, stirred at 80°C and 500 rpm for 4 h, washed by centrifugation with ethanol 4 times, and dried in a vacuum drying oven at 110°C for 12 h;

[0097] (2) calcining the powder at 700° C. for 4 h in a muffle furnace at a heating rate of 2° C. / min to obtain cobalt aluminum spinel;

[0098] The catalyst was pre-reduced with hydrogen before the reaction test. The total air velocity of the feed gas was 8000 mL / g / h. The pretreatment condition was 600°C and the reduction was 4 hours. After the temperature dropped to room temperature, the reaction gas was introduced into the fixed bed reactor to evaluate the reaction performance. The reaction temperature was 260°C, the reaction pressure was 3 MPa, the air velocity was 6000 mL / g / h, and the gas used was CO. 2 / H 2 The volume ratio of is 24:72. The reaction performance test results are shown in Table 1.

[0099] Table 1

[0100]

[0101]

[0102] As can be seen from Table 1, the catalyst prepared by the present invention can achieve the technical effect of hydrogenating carbon dioxide to synthesize ethanol. Compared with the catalytic performance of the comparative catalyst, on the basis of constructing the cobalt-aluminum spinel structure, the conversion rate of carbon dioxide and the selectivity of ethanol can be significantly improved by regulating the ratio of cobalt and aluminum, the hydrogen pre-reduction temperature and the introduction of alkali metal. Taking Example 4 as an example, the conversion rate of carbon dioxide is 41%, the selectivity of total alcohol can reach 78%, and the selectivity of ethanol reaches 64%, which also shows that the preparation method of the catalyst of the present invention can effectively improve the catalytic performance of selective hydrogenation of carbon dioxide to ethanol.

[0103] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. An alkali metal-supported cobalt-based catalyst, characterized in that: It includes cobalt aluminum spinel and alkali metal loaded on cobalt aluminum spinel. The active center cobalt of cobalt aluminum spinel exists in the form of CoAl2O4 spinel structure and the other part exists in the form of zero-valent Co 0 Form exists.

2. The alkali metal-supported cobalt-based catalyst according to claim 1, characterized in that The loading amount of the alkali metal is 5 wt% to 15 wt% based on the mass of the cobalt aluminum spinel.

3. The alkali metal-supported cobalt-based catalyst according to claim 1, characterized in that Cobalt in the form of CoAl2O4 spinel structure and zero-valent Co 0 The molar ratio of cobalt in the form of is 15:1 to 2:

1.

4. A method for preparing an alkali metal-supported cobalt-based catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Dissolve cobalt salt and aluminum isopropoxide in ethylene glycol, stir under heating conditions, wash with ethanol by centrifugation, and dry in a vacuum drying oven; calcine the dried powder in a muffle furnace at high temperature to obtain cobalt aluminum spinel; S2. Dissolve cobalt aluminum spinel and alkali metal chloride in deionized water, stir evenly, stir under heating conditions to completely evaporate the deionized water, and then place in a vacuum drying oven for drying; place the dried powder in a muffle furnace for high-temperature calcination, and then perform hydrogen reduction treatment to obtain an alkali metal-loaded cobalt-based catalyst.

5. The preparation method according to claim 4, characterized in that: In step S1, the cobalt salt includes one or more of cobalt nitrate or its hydrate, cobalt carbonate or its hydrate, and cobalt sulfate or its hydrate; In step S1, the molar ratio of cobalt in the cobalt salt to aluminum in aluminum isopropoxide is 1:2 to 1:

8.

6. The preparation method according to claim 4, characterized in that: In step S1, the stirring heating temperature is 30°C to 90°C, the stirring speed is 200rpm to 600rpm, and the stirring time is 2 to 6h; In step S1, the high temperature calcination temperature is 400°C to 800°C, the calcination time is 1h to 8h, and the heating rate is 1°C / min to 10°C / min.

7. The preparation method according to claim 4, characterized in that: In step S2, the alkali metal chloride includes one or more of lithium chloride, sodium chloride, and potassium chloride; In step S2, the amount of alkali metal added is 5wt%-15wt% based on the mass of cobalt aluminum spinel.

8. The preparation method according to claim 4, characterized in that: In step S2, the heating and stirring temperature is 50°C to 100°C, and the stirring rate is 200rpm to 600rpm; In step S2, the high temperature calcination temperature is 200°C to 800°C, the calcination time is 1h to 8h, and the heating rate is 1°C / min to 10°C / min; In step S2, the conditions for hydrogen reduction treatment are: space velocity of 3000mL / g / h to 10000mL / g / h, reduction temperature of 250°C to 800°C, and reduction time of 1h to 6h.

9. Use of the alkali metal-supported cobalt-based catalyst according to any one of claims 1 to 3 in the preparation of ethanol by catalytic reaction of carbon dioxide hydrogenation.

10. The use according to claim 9, characterized in that: The conditions of the catalytic reaction are: reaction temperature of 200-400°C, reaction pressure of 2-4MPa, total space velocity of raw gas of 3000-8000mL / g / h, and the gas used is a mixture of CO2 and H2, wherein the volume ratio of CO2 to H2 is 1:1-1:4; The catalyst was pre-reduced with hydrogen before the reaction test. The reduction conditions were as follows: hydrogen space velocity of 3000 mL / g / h to 10000 mL / g / h, reduction temperature of 250°C to 400°C, and reduction time of 1h to 6h.

Citation Information

Patent Citations

  • Preparation of mesoporous metal / cobalt aluminate dual-function catalyst and application

    CN101637723A

  • Preparation method and application of cobalt-based catalyst for catalyzing carbon dioxide to prepare ethanol

    CN108380216A

  • Application of catalyst in Fischer-Tropsch synthesis reaction

    CN112892538A

  • Application of cobalt-based catalyst in Fischer-Tropsch synthesis reaction

    CN113117691A

  • Preparation method and application of back-loaded cobalt-based catalyst for synthesizing higher alcohol through hydrogenation of carbon dioxide

    CN116393136A